Does Foreign Aid Improve Gender Performance in Recipient Countries?. (14th July 2020) - Bali Swain, Ranjula; Garikipati, Supriya; Wallentin, Fan Yang
Abstract: An explicit goal of foreign aid is to promote female empowerment and gender equality in developing countries. We investigate if foreign aid achieves this intended goal by examining its impact on gender performance of recipient countries at the country level. Employing structural equation models, our results suggest that aid alone, even when targeted to directly improve gender outcomes, is unlikely to shift systemic inequalities. Aid will need to bolster civil society efforts that challenge institutional structures and norms in order to impact gender outcomes at country level. © 2020 The Authors. Journal of International Development published by John Wiley & Sons Ltd